2006
DOI: 10.1002/ejsp.322
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between and within groups: the influence of individualist and collectivist group norms

Abstract: The power of individualist and collectivist group norms to influence intergroup and inter-individual differentiation was examined in three studies. Study 1 revealed that intergroup differentiation was lower when group norms prescribed individualism than when they prescribed collectivism. However, inter-individual differentiation was higher when group norms endorsed individualism than when they promoted collectivism. In Studies 2 and 3 we found evidence for the moderating effect of group salience on the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 33 publications
1
31
0
1
Order By: Relevance
“…Heterogeneous groups can function as well as homogeneous groups, as long as they can use their diversity. For example, research has found that group norms of independence and individualism, or social values of diversity increase appreciation of heterogeneity within groups (Homan et al, 2007;Jetten, McAuliffe, Hornsey, & Hogg, 2006;Jetten et al, 2002). Moving beyond this work, our studies show that social identity emerges in heterogeneous groups where no prior norms or values of diversity had been activated or imposed.…”
Section: Discussionmentioning
confidence: 54%
“…Heterogeneous groups can function as well as homogeneous groups, as long as they can use their diversity. For example, research has found that group norms of independence and individualism, or social values of diversity increase appreciation of heterogeneity within groups (Homan et al, 2007;Jetten, McAuliffe, Hornsey, & Hogg, 2006;Jetten et al, 2002). Moving beyond this work, our studies show that social identity emerges in heterogeneous groups where no prior norms or values of diversity had been activated or imposed.…”
Section: Discussionmentioning
confidence: 54%
“…For example, group norms that prescribe individualism might help to prevent groupthink (Janis, 1972; see also Postmes et al, 2001). Recent research also shows that group norms prescribing individualism or collectivism can aVect the manner in which positive diVerentiation among group members occurs (Jetten, McAuliVe, Hornsey, & Hogg, 2005). Individualist norms weaken intergroup diVerentiation, but strengthen interindividual diVerentiation, compared to collectivist norms.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 96%
“…Social identity perspectives encourage us to integrate knowledge across different levels of analysis in order to deepen our understanding of global and intergroup issues such as climate change (Batalha & Reynolds, 2012 ). The social identity perspective on "individuals as in-group members" offers us a novel starting point for empirical research, as well as a comprehensive, parsimonious, and generalisable account of global climate change-beyond individual behaviour in individualistic countries Jetten, McAuliffe, Hornsey, & Hogg, 2006 ).…”
Section: Moving Beyond Individualistic Viewsmentioning
confidence: 99%